The continuous signal f(t) = cos(πt/2) sampled at 1 second intervals starting from t = 0.
(a) Find the Laplace transform of the sampled signal f*(t)
"f^*(s)=\\int\\limits_0^1\\cos\\frac{\\pi t}{2}e^{-ts}dt=-\\frac{1}{s}\\int\\limits_0^1\\cos\\frac{\\pi t}{2}de^{-ts}="
"[-\\frac{1}{s}\\cos\\frac{\\pi t}{2}e^{-ts}]_0^1+\\frac{1}{s}\\int\\limits_0^1e^{-ts}d\\cos\\frac{\\pi t}{2}=" "\\frac{1}{s}-\\frac{\\pi}{2s}\\int\\limits_0^1\\sin\\frac{\\pi t}{2}e^{-ts}dt"
"\\int\\limits_0^1\\sin\\frac{\\pi t}{2}e^{-ts}dt=-\\frac{1}{s}\\int\\limits_0^1\\sin\\frac{\\pi t}{2}de^{-ts}=""[-\\frac{1}{s}\\sin\\frac{\\pi t}{2}e^{-ts}]_0^1+\\frac{1}{s}\\int\\limits_0^1e^{-ts}d\\sin\\frac{\\pi t}{2}="
"=-\\frac{1}{s}e^{-s}+\\frac{\\pi}{2s}\\int\\limits_0^1\\cos\\frac{\\pi t}{2}e^{-ts}dt=-\\frac{1}{s}e^{-s}+\\frac{\\pi}{2s}f^*(s)"
Hence, "f^*(s)=\\frac{1}{s}-\\frac{\\pi}{2s}\\left(-\\frac{1}{s}e^{-s}+\\frac{\\pi}{2s}f^*(s)\\right)"
"(1+\\frac{\\pi^2}{4s^2})f^*(s)=\\frac{1}{s}+\\frac{\\pi}{2s^2}"
Therefore, "f^*(s)=\\frac{\\frac{1}{s}+\\frac{\\pi}{2s^2}}{1+\\frac{\\pi^2}{4s^2}}=\\frac{2\\pi+4s}{\\pi^2+4s^2}"
Comments
Leave a comment